Nanobiosensors in neurodegenerative disease diagnosis: A promising pathway for early detection - Shikha Yadav; Sarad Pawar Naik Bukke; Shatrudhan Prajapati; Ajay Pal Singh; Ananda Kumar Chettupalli; Buyinza Nicholas (Digital Health)
Neurodegenerative diseases, including Alzheimer's and Parkinson's, are characterized by progressive neuronal loss, leading to cognitive and motor impairments. Early diagnosis remains a challenge due to the slow progression of symptoms and the limitations of current diagnostic methods. Nanobiosensors, leveraging the high sensitivity and specificity of nanotechnology, offer a promising, noninvasive, and cost-effective approach for detecting disease biomarkers at ultra-low concentrations. This review highlights recent advancements in nanobiosensor technology, including the integration of gold nanoparticles, quantum dots, and carbon nanotubes, which have significantly enhanced biomarker detection precision. Furthermore, it examines the advantages of nanobiosensors over traditional diagnostic techniques, such as improved sensitivity, rapid detection, and minimal invasiveness. The potential of these innovative sensors to revolutionize early disease detection and improve patient outcomes is discussed, along with existing challenges in clinical translation, including stability, reproducibility, and regulatory considerations. Addressing these limitations will be crucial for integrating nanobiosensors into routine clinical practice and advancing personalized medicine for neurodegenerative disorders.